WINETA – THE LITERARY “LOST SPACE” OF THE WESTERN SLAVS? REFLECTIONS ON THE SELECTED EXAMPLES FROM THE WEST SLAVIC LITERATURES - Derlatka, Tomasz (Porównania, 2013)
The purpose of the article is to present the selected West Slavic literary works that have taken the issue of the legendary Wineta. The author has made efforts to determine the extent of the occurrence of the motif of Wineta in particular literatures, to demonstrate mutual convergences and divergences, to present the most interesting modifications of the protovariation. The analysis of the subject showed profound differences in the sematisation of the Wineta theme between specific literatures. The most interesting elaborations of the Wineta theme are found in “small” West Slavonic literatures (Upper Lusatian and Kashubian). In the first one, the semantics of the Wineta, which was transferred onto a “national” plane and which is at risk of being flooded by the sea (first by the Germanic one [J. Bart-Ćišinski] of the post-1945 socialist realist industry [A. Stachowa]) itself becomes the diaspora. In the Kashubian literature, the Wineta motif was exploited as the basis for its own mythopoeia realized in the legend of the Old Hel swallowed by the sea.